(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Obesity is currently one of the most common metabolic disorders in the body. Experimental alimentary obesity leads to changes in the structural and functional organization of the liver, including disorders of blood circulation and lymph flow, the development of fatty degeneration in the parenchyma of the organ. The central links in the metabolism of proteins, lipids and carbohydrates take place in the liver, and it is also a barrier to all foreign substances entering the body. The problem of studying morphological changes in organs in obesity based on the effective use of medicinal plants as a means for the treatment and prevention of diseases is urgent. To assess the morphological changes in the liver in obesity, a natural medicinal plant "Frangula alnus" was used in the experiment. Changes in the structural organization of the liver are reflected in its functional state and the process of lipid metabolism. The article studies pathological changes in the activity of liver cells, which lead to a decrease in the detoxification function of the liver and destructive changes. Feeding rats with fatty food in combination with powder from the bark of the medicinal plant buckthorn "Frangula alnus" showed that the use of such a combination in the diet contributes to the normalization of morphological processes and restoration of the structural and functional organization of the rat liver.